Registration of 'USDA Fortress' winter feed barley with multiple aphid resistance. Issue 3 (18th July 2022) - Mornhinweg, Dolores W.; Carver, Brett Frederick; Springer, Tim
Abstract: 'USDA Fortress' (Reg. no. CV‐375, PI 696161), a multiple aphid‐resistant, high yielding, six‐rowed, mid‐season–maturing, winter feed barley ( Hordeum vulgare L.) adapted to the Southern Plains, was developed and released by USDA‐ARS in Stillwater, OK. USDA Fortress is highly resistant to Russian wheat aphid [RWA; Diuraphis noxia (Kurdjumov)] and greenbug [ Shizaphis graminum (Rondani)], with seedling resistance to the new invasive pest, hedgehog grain aphid [HGA; Sipha maydis (Passerini)]. USDA Fortress has the pedigree 'Post 90' * 4/R012. Recurrent parent Post 90 has Rsg1 resistance to greenbug, and R012 is an unadapted RWA‐resistant germplasm line selected by USDA‐ARS Stillwater from PI 10706. Post 90 and USDA Fortress rate 2 on Starks' greenbug resistance scale of 1–9, while USDA Fortress and R012 rate a 3 on Websters Russian wheat aphid resistance scale of 1–9, where 1 is immune and 9 is dead on both scales. Over 17 location‐years, in the absence of aphids, grain yield of USDA Fortress was 19 and 12% greater than 'Thoroughbred' and Post 90, respectively. USDA Fortress has average test weight of 60 kg hl –1 and has stable grain yield over state‐wide variability in climatic conditions. USDA Fortress is the first multiple‐aphid resistant barley cultivar in the United States. Core Ideas: USDA Fortress has a high level of resistance to multiple aphid pests of barley. USDA Fortress is high yielding across varied climatic conditions. USDA Fortress is a non–genetically modified organism feed barley competitive with other feed grains for forage.